Partially zwitterionic polyion liquid material, humidity sensor with full humidity sensing characteristic and preparation method of humidity sensor
By grafting sulfonic acid groups on the branch chain of polyionic liquid material to form zwitterionic polymer chains, the problems of long response recovery time, large humidity hysteresis and poor stability of existing humidity sensors are solved, and high sensitivity, rapid response and Humidity sensing effect with low humidity stagnation.
Patent Information
- Application Number
- CN202411737177.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-11
AI Technical Summary
Existing polyion liquid-based humidity sensors have problems such as long response recovery time, large humidity hysteresis and poor long-term stability, which is difficult to meet the needs of high sensitivity and rapid response.
Through the olefin-thio click chemical reaction under ultraviolet excitation, sulfonic acid groups are grafted on the branch chain of the polyion liquid to form zwitterionic polymer chains, thereby realizing partial zwitterionic ionization and preparing a poly with excellent humidity sensing characteristics Ionic liquid material.
It improves the sensitivity and response recovery speed of the humidity sensor, reduces humidity hysteresis, and enhances long-term stability, achieving efficient humidity detection within the entire humidity range.
Smart Images

Figure CN119409972A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of humidity sensors, and in particular relates to a partially zwitterionized polyionic liquid material, a humidity sensor with full humidity sensing characteristics, and a preparation method thereof. Background Art
[0002] Humidity, as the main parameter to measure the dryness and wetness of air, is inseparable from human daily life. The detection of environmental humidity is widely used in meteorological environment monitoring, industrial production, agricultural planting, aerospace and medical fields. At a time when artificial intelligence is rapidly maturing and the Internet of Things is developing rapidly, accurate and rapid monitoring of environmental humidity is particularly important.
[0003] There are many methods currently used to detect humidity, including spectroscopy, weight method, and surface acoustic wave method. These methods can accurately measure the humidity of the environment, but there are still problems such as long time consumption, high cost, and complex operation. Impedance-type humidity sensors have the advantages of simple preparation, low cost, and small size, and are a technology with great application prospects in the field of humidity detection. At present, polyionic liquid materials, as a new type of material that combines the properties of polymers and ionic liquid materials, have been applied to impedance-type humidity sensors. However, the above-mentioned sensors still have the disadvantages of long response recovery time, large hysteresis, and poor long-term stability. Therefore, a new type of humidity-sensitive material is designed, which can improve the sensitivity of polyionic liquid-based humidity sensors while reducing the response recovery time and hysteresis of polyionic liquid-based humidity sensors, which is of great significance for obtaining polyionic liquid-based humidity sensors with excellent performance. Summary of the invention
[0004] The purpose of the present invention is to provide a partially zwitterionized polyionic liquid material, a humidity sensor with full humidity sensing characteristics and a preparation method thereof.
[0005] The present invention prepares a polyionic liquid material by using an olefin-thiol click chemistry reaction under ultraviolet light excitation, and forms a zwitterionic polymer chain by grafting a sulfonic acid group on the polyionic liquid side chain, thereby partially zwitterionizing the polyionic liquid material. The partially zwitterionized polyionic liquid material of the present invention is obtained by the following steps (unless otherwise specified, the solutions of the present invention are all methanol solutions):
[0006] (1) dissolving 80-90 mg of an ionic liquid in a methanol solvent to obtain an ionic liquid solution with a concentration of 90-110 mg / mL, wherein the ionic liquid is 1-allyl-3-vinylimidazolium bromide or 1-allyl-3-vinylimidazolium chloride;
[0007] (2) subjecting the ionic liquid solution obtained in step (1) to ultrasonic treatment for 2 to 5 minutes to obtain a uniformly dispersed ionic liquid solution;
[0008] (3) adding 60 to 105 mg of a polymerization monomer to the uniformly dispersed ionic liquid solution obtained in step (2), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate;
[0009] (4) adding 0.1 to 45.0 mg of a zwitterionic polymerization monomer to the mixed solution obtained in step (3), wherein the zwitterionic polymerization monomer is sodium 2-mercaptoethanesulfonate;
[0010] (5) adding methanol solvent to the solution obtained in step (4), wherein the total amount of methanol solvent used in step (1) and step (5) is 900 to 1100 μL, and then ultrasonicating the obtained solution for 2 to 5 minutes to obtain a uniformly dispersed mixture solution;
[0011] (6) adding 1.5 to 2.5 mg of an ultraviolet light curing initiator to the uniformly dispersed mixed solution obtained in step (5), wherein the ultraviolet light curing initiator is benzoin dimethyl ether, to obtain a polyionic liquid precursor solution;
[0012] (7) subjecting the polyionic liquid precursor solution obtained in step (6) to ultrasonic treatment for 2 to 5 minutes to obtain a uniformly dispersed polyionic liquid precursor solution;
[0013] (8) placing the uniformly dispersed polyionic liquid precursor solution obtained in step (7) in a CL-1000 ultraviolet crosslinking irradiator and irradiating with 365 nm ultraviolet light for 20 to 40 minutes to obtain the partially zwitterionized polyionic liquid material.
[0014] The humidity sensor with full humidity (11% to 95% RH) sensing characteristics described in the present invention is composed of a ceramic substrate with 2 to 5 pairs of graphite carbon interdigital electrodes on the surface, and a sensitive layer (thickness 10 to 100 μm) dripped on the ceramic substrate and the graphite carbon interdigital electrodes; the graphite carbon interdigital electrodes are 5 to 10 mm long, 3 to 7 mm wide, 0.2 to 1 mm thick, and the electrode spacing is 0.2 to 1 mm. The sensitive layer material is a partially zwitterionized polyionic liquid material prepared by the present invention. After the sensitive layer material contacts water molecules in the air, it will adsorb water molecules, and the impedance value of the humidity sensitive layer between the graphite carbon interdigital electrodes will change. By comparing the change in the impedance value of the humidity sensitive layer between the graphite carbon interdigital electrodes measured by an impedance analyzer before and after the humidity sensor absorbs moisture, the sensitivity of the sensor can be obtained (test voltage: the voltage applied to the two ends of the interdigital electrodes is an AC voltage of 1 volt and 1000 Hz). Sensitivity is calculated by dividing the difference between the impedance value of the sensor in the initial relative humidity (11%) test environment and the impedance value in the highest relative humidity (95%) test environment by the impedance value in the highest relative humidity (95%) test environment. Hysteresis is the maximum relative humidity difference between the adsorption sensitivity curve of the humidity sensor at 11% to 95% relative humidity and the desorption sensitivity curve at 95% to 11% relative humidity at the same impedance value, which is drawn by the test relationship between relative humidity and impedance value. Response time refers to the time taken for the impedance value of the humidity sensor to decrease by 90% after it is placed in an environment with 95% relative humidity from an environment with 11% relative humidity; recovery time refers to the time taken for the impedance value of the humidity sensor to increase by 90% after it is placed in an environment with 11% relative humidity from an environment with 95% relative humidity.
[0015] The humidity sensor described in the present invention is an impedance-type humidity sensor, and its output signals are all impedance signals, which are obtained by testing with an impedance analyzer.
[0016] The method for preparing a humidity sensor with full humidity sensing characteristics described in the present invention comprises the following steps:
[0017] (1) Pipette 2 to 5 μL of a uniformly dispersed polyionic liquid precursor solution and drop-coat it onto a ceramic substrate having 2 to 5 pairs of graphite carbon interdigital electrodes on its surface;
[0018] (2) placing the device obtained in step (1) in a CL-1000 UV cross-linking irradiator and irradiating with 365 nm UV light for 20 to 40 min to obtain a partially zwitterionized polyionic liquid sensitive layer with a thickness of 10 to 100 μm on the ceramic substrate and the graphite carbon interdigital electrode;
[0019] (3) The device obtained in step (2) is aged at a relative humidity of 65-85% for 1-12 hours, thereby obtaining an impedance-type humidity sensor with full humidity sensing characteristics based on a partially zwitterionized polyionic liquid sensitive layer.
[0020] The advantages of the present invention are:
[0021] 1) The raw materials and the ceramic substrate with graphite carbon interdigital electrodes of the present invention can be purchased from the market, with low raw material cost, high yield, good structural consistency, and suitable for mass production;
[0022] 2) The humidity sensor prepared by the present invention has a simple manufacturing process and a small size, and is suitable for industrial batch production;
[0023] 3) The impedance-type humidity sensor prepared by the present invention has excellent humidity-sensitive properties in the full humidity range, including high sensitivity, high stability, small humidity hysteresis and fast response recovery characteristics, which solves the problems of low sensitivity, slow recovery and poor stability of most polymer-based humidity sensors when detecting humidity;
[0024] 4) The present invention grafts zwitterionic polymers on the side chains of polyionic liquid materials, and generates a higher concentration of free ions per unit volume of ionic liquid after adsorbing water molecules. This increase in ion concentration further improves the response value of the polyionic liquid-based impedance-type humidity sensor, while reducing the response time of the polyionic liquid-based impedance-type humidity sensor;
[0025] 5) The zwitterionic polymer grafted in the side chain of the partially zwitterionized polyionic liquid material in the present invention is a sulfobetaine zwitterionic polymer, which has the characteristics of self-association and anti-electrolyte, and has strong hydrophobic properties. After the partially zwitterionized polyionic liquid material in the present invention adsorbs water molecules, a large number of free anions and cations are ionized to expose the sulfobetaine zwitterionic polymer on the side chain, forming a large number of hydrophobic zwitterionic polymers, which improve the hydrophobic properties of the polyionic liquid in the process of desorption of water molecules, thereby reducing the recovery time of the polyionic liquid-based impedance humidity sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the infrared absorption spectrum of the partially zwitterionized polyionic liquid material prepared in Example 3;
[0027] Figure 2 is the frequency characteristic curve of the impedance humidity sensor prepared in Example 3 at a relative humidity of 11% to 95%;
[0028] Figure 3is the humidity sensitivity characteristic curve of the impedance-type humidity sensor prepared in Examples 1 to 4 at a relative humidity of 11% to 95%;
[0029] Figure 4 1 is the response recovery curve of the impedance humidity sensor prepared in Example 3 at 11% relative humidity and 95% relative humidity;
[0030] Figure 5 This is a multiple measurement repeatability curve of the impedance humidity sensor prepared in Example 3 at 11% relative humidity and 95% relative humidity;
[0031] Figure 6 is the hysteresis curve of the impedance-type humidity sensor prepared in Example 3 at a relative humidity of 11% to 95%;
[0032] Figure 7 This is a 30-day long-term stability test of the impedance-type humidity sensor prepared in Example 3 at a relative humidity of 11% to 95%. DETAILED DESCRIPTION
[0033] Example 1
[0034] (1) dissolving 87.7 mg of ionic liquid in 877 μL of methanol solvent to prepare a 100 mg / mL ionic liquid solution, wherein the ionic liquid is 1-allyl-3-vinylimidazolium bromide;
[0035] (2) subjecting the solution obtained in step (1) to ultrasonic treatment for 2.5 min to obtain a uniformly dispersed ionic liquid solution;
[0036] (3) adding 100 mg of a polymerization monomer to the uniformly dispersed ionic liquid solution obtained in step (2), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate;
[0037] (4) adding 0.1 mg of a zwitterionic polymerization monomer to the mixed solution obtained in step (3), wherein the zwitterionic polymerization monomer is sodium 2-mercaptoethanesulfonate;
[0038] (5) adding 123 μL of methanol solvent to the solution obtained in step (4), and ultrasonicating the resulting solution for 2.5 min to obtain a uniformly dispersed mixture solution;
[0039] (6) adding 2.1 mg of ultraviolet light curing initiator to the mixed solution of step (5), wherein the ultraviolet light curing initiator is benzoin dimethyl ether, to obtain a polyionic liquid precursor solution;
[0040] (7) ultrasonically treating the polyionic liquid precursor solution obtained in step (6) for 2.5 min to obtain 1000 μL of a uniformly dispersed polyionic liquid precursor solution;
[0041] (8) 998 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (7) was transferred to a CL-1000 UV crosslinking irradiator and irradiated with 365 nm UV light for 25 min to obtain 190 mg of partially zwitterionized polyionic liquid material;
[0042] (9) Pipette 2 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (7) and drop-coat it onto a ceramic substrate having three pairs of graphite carbon interdigital electrodes on the surface. The interdigital electrodes are 7 mm long, 5 mm wide, and 0.6 mm thick, and the interdigital electrode spacing is 0.5 mm;
[0043] (10) placing the device obtained in step (9) in a CL-1000 UV crosslinking irradiator and irradiating with 365 nm UV light for 25 min;
[0044] (11) The device obtained in step (10) is aged at 85% relative humidity for 1 hour to obtain an impedance-type humidity sensor based on a partially zwitterionized polyionic liquid sensitive layer with a sensitive layer thickness of 10 μm.
[0045] Example 2
[0046] Steps (1) to (2) are the same as those in Example 1;
[0047] (3) adding 90 mg of a polymerization monomer to the solution of step (2), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate;
[0048] (4) adding 13.5 mg of a zwitterionic polymerization monomer to the mixed solution of step (3), wherein the zwitterionic polymerization monomer is sodium 2-mercaptoethanesulfonate;
[0049] Steps (5) to (7) are the same as those in Example 1;
[0050] (8) 998 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (7) was transferred to a CL-1000 UV crosslinking irradiator and irradiated with 365 nm UV light for 25 min to obtain 194 mg of partially zwitterionized polyionic liquid material;
[0051] Steps (9) to (11) are the same as those in Example 1, thereby obtaining an impedance-type humidity sensor based on a partially zwitterionized polyionic liquid sensitive layer with a sensitive layer thickness of 11 μm.
[0052] Example 3
[0053] Steps (1) to (2) are the same as those in Example 1;
[0054] (3) adding 80 mg of a polymerization monomer to the solution of step (2), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate;
[0055] (4) adding 27.0 mg of a zwitterionic polymerization monomer to the mixed solution of step (3), wherein the zwitterionic polymerization monomer is sodium 2-mercaptoethanesulfonate;
[0056] Steps (5) to (7) are the same as those in Example 1;
[0057] (8) 998 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (7) was transferred to a CL-1000 UV crosslinking irradiator and irradiated with 365 nm UV light for 25 min to obtain 197 mg of partially zwitterionized polyionic liquid material;
[0058] Steps (9) to (11) are the same as those in Example 1, thereby obtaining an impedance-type humidity sensor based on a partially zwitterionized polyionic liquid sensitive layer with a sensitive layer thickness of 12 μm.
[0059] Example 4
[0060] Steps (1) to (2) are the same as those in Example 1;
[0061] (3) adding 70 mg of a polymerization monomer to the solution of step (2), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate;
[0062] (4) adding 40.5 mg of a zwitterionic polymerization monomer to the mixed solution of step (3), wherein the zwitterionic polymerization monomer is sodium 2-mercaptoethanesulfonate;
[0063] Steps (5) to (7) are the same as those in Example 1;
[0064] (8) 998 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (7) was transferred to a CL-1000 UV crosslinking irradiator and irradiated with 365 nm UV light for 25 min to obtain 200 mg of a polyionic liquid material containing a hydrophobic component;
[0065] Steps (9) to (11) are the same as those in Example 1, thereby obtaining an impedance-type humidity sensor based on a partially zwitterionized polyionic liquid sensitive layer with a sensitive layer thickness of 12 μm.
[0066] The Fourier infrared spectrum of the partially zwitterionized polyionic liquid material prepared in Example 3 is as follows: Figure 1 The characteristic peak of carbon-carbon double bond is at 3140 cm -1 The characteristic peak of carbon-oxygen double bond is at 1643 cm -1 The characteristic peak of thiol appears at 2967 cm-1 、640cm -1 and 1256cm -1 The skeleton vibration peak and stretching vibration peak of the imidazole ring appear at 1568 cm -1 and 1172cm -1 The successful preparation of the polyionic liquid host was demonstrated. -1 The peak at 1103 cm is the characteristic peak of the sulfur-oxygen double bond in the sulfonic acid group, and the characteristic peak of the sulfur-oxygen single bond in the sulfonic acid group appears at 1103 cm -1 The successful grafting of zwitterionic polymer branches was demonstrated.
[0067] The frequency characteristic curve of the impedance humidity sensor prepared in Example 3 in the relative humidity range of 11 to 95% is as follows: Figure 2 As shown. Figure 2 It can be seen that for the impedance-type low humidity sensor based on polyionic liquid material containing hydrophobic components, when the test frequency exceeds 10kHz, the sensitivity is less than 200; when the test frequency is lower than 100Hz, the sensor impedance value is unstable, so 1kHz is selected as the optimal operating frequency.
[0068] The humidity sensitivity characteristic curves of the impedance-type humidity sensors prepared in Examples 1 to 4 in the relative humidity range of 11 to 95% are as follows: Figure 3 The sensitivity of the four humidity sensors in the relative humidity range of 11-95% are 1180.9, 3694.1, 4862.8, and 7004.7, respectively, indicating that the response value of the humidity sensor gradually increases with the increase of the concentration of the zwitterionic polymer side chains, proving that the zwitterionic polymer grafted with the side chains of the polyionic liquid material can improve the response value of the polyionic liquid-based impedance humidity sensor.
[0069] The response recovery curve of the impedance humidity sensor prepared in Example 3 between 11% and 95% relative humidity is as follows: Figure 4 The response and recovery time of the sensor in the test were 1 second and 15 seconds respectively, which shows that the zwitterionic polymer grafted with the branched chain of the polyionic liquid material can enhance the response recovery characteristics of the polyionic liquid material and reduce the response recovery time of the polyionic liquid-based impedance humidity sensor.
[0070] The multiple response recovery curves of the impedance humidity sensor prepared in Example 3 between 11% and 95% relative humidity are shown in FIG. Figure 5 The sensor response value did not change significantly during the 5 cycle tests, and the sensor baseline did not change significantly, which further demonstrated that the impedance-type humidity sensor based on partially zwitterionized polyionic liquid materials has good stability in humidity measurement.
[0071] The hysteresis curve of the impedance humidity sensor prepared in Example 3 in the relative humidity range of 11 to 95% is as follows: Figure 6 As shown in the figure, it can be seen that the humidity sensor has a very small hysteresis of 0.6% relative humidity in the relative humidity range of 11% to 95%.
[0072] The impedance humidity sensor prepared in Example 3 was tested for 30 days of long-term stability in the relative humidity range of 11 to 95%. Figure 7 During the test, the impedance value of the sensor at the same relative humidity did not change much, proving that the impedance-type humidity sensor based on partially zwitterionized polyionic liquid materials has good long-term stability in humidity detection.
Claims
1. A partially zwitterionized polyionic liquid material, which is prepared by the following steps: (1) dissolving 80-90 mg of an ionic liquid in a methanol solvent to obtain an ionic liquid solution with a concentration of 90-110 mg / mL, wherein the ionic liquid is 1-allyl-3-vinylimidazolium bromide or 1-allyl-3-vinylimidazolium chloride; (2) subjecting the ionic liquid solution obtained in step (1) to ultrasonic treatment for 2 to 5 minutes to obtain a uniformly dispersed ionic liquid solution; (3) adding 60 to 105 mg of a polymerization monomer to the uniformly dispersed ionic liquid solution obtained in step (2), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate; (4) adding 0.1 to 45.0 mg of a zwitterionic polymerization monomer to the mixed solution obtained in step (3), wherein the zwitterionic polymerization monomer is sodium 2-mercaptoethanesulfonate; (5) adding methanol solvent to the solution obtained in step (4), wherein the total amount of methanol solvent used in step (1) and step (5) is 900 to 1100 μL, and then ultrasonicating the obtained solution for 2 to 5 minutes to obtain a uniformly dispersed mixture solution; (6) adding 1.5 to 2.5 mg of an ultraviolet light curing initiator to the uniformly dispersed mixed solution obtained in step (5), wherein the ultraviolet light curing initiator is benzoin dimethyl ether, to obtain a polyionic liquid precursor solution; (7) subjecting the polyionic liquid precursor solution obtained in step (6) to ultrasonic treatment for 2 to 5 minutes to obtain a uniformly dispersed polyionic liquid precursor solution; (8) Irradiating the uniformly dispersed polyionic liquid precursor solution obtained in step (7) with 365 nm ultraviolet light for 20 to 40 minutes to obtain the partially zwitterionized polyionic liquid material.
2. A method for preparing a humidity sensor with full humidity sensing characteristics, the steps of which are as follows: (1) pipetting 2 to 5 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (7) of claim 1, and drop-coating it onto a ceramic substrate having 2 to 5 pairs of graphite carbon interdigital electrodes on its surface; (2) irradiating the device obtained in step (1) with 365 nm ultraviolet light for 20 to 40 min to obtain a partially zwitterionized polyionic liquid sensitive layer on the ceramic substrate and the graphite carbon interdigital electrode; (3) The device obtained in step (2) is aged at a relative humidity of 65-85% for 1-12 hours, thereby obtaining an impedance-type humidity sensor with full humidity sensing characteristics based on a partially zwitterionized polyionic liquid sensitive layer.
3. The method for preparing a humidity sensor having full humidity sensing characteristics as claimed in claim 2, characterized in that: The graphite carbon interdigital electrode has a length of 5 to 10 mm, a width of 3 to 7 mm, a thickness of 0.2 to 1 mm, and an electrode spacing of 0.2 to 1 mm.
4. The method for preparing a humidity sensor having full humidity sensing characteristics according to claim 2, characterized in that: The thickness of the partially zwitterionized polyionic liquid sensitive layer is 10 to 100 μm.
5. A humidity sensor with full humidity sensing characteristics, characterized in that: The method is prepared by the method described in claim 2, 3 or 4.